Burden of liver cancer resulting from different etiologies in China from 1990 to 2021 and prediction to 2031 - Meiling Zhang; Yan Tan; Zegui Fang; Feng Li; Xiaoxiao Chen; Xiaoshan Chen; Yongyue Deng; Siyang Huang (PLoS ONE, 2025)
Liver cancer (LC) imposes a considerable disease burden in China, with diverse causes contributing to varying proportions of LC cases. Adjusting future public health strategies for the allocation of resources to interventions aimed at different causes of LC is a subject that demands resolution in order to maximize health benefits. Employing the Global Burden of Disease (GBD) 2021, we analyzed the burden of LC in China attributed to different causes. Utilize joinpoint to evaluate the trend of the disease burden of LC. The Bayesian model for age-period-cohort (BAPC) was adopted to forecast the burden. The overall trend of the age-standardized rates of incidence, mortality, and disability-standardized life years (ASIR, ASMR, and ASDR) of LC were descend in China from 1990 to 2021. HBV, HCV, alcohol and non-alcoholic steatohepatitis (NASH) constitute the four principal causes of the LC burden. The ASIR, ASMR, and ASDR of LC caused by HBV and HCV showed a downward trend. The ASIR of LC caused by alcohol and NASH were associated with an increased. It was anticipated that the burden of ASIR and ASMR for male, female, and the entire population in China will persistently decline until 2031. In conclusion, the burden of LC has displayed a downward trend in China from 1990 to 2021; HBV, HCV, alcohol, and NASH were the main causes of LC; the burden of LC is expected to further decline by 2031.